PENGARUH DURASI BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS 5 LEDOK 006 SALATIGA - Sari, Bernadetha Titis Wulan (Jurnal Review Pendidikan dan Pengajaran, 2019)
This study discusses how to learn mathematics which was reviewed in class 5 students of SD Negeri Ledok 06 Salatiga. This research was conducted through qualitative methods. Data sources were obtained through two sources, namely primary data obtained from research subjects by using data retrieval tools directly on the subject of class 5 information sources. Secondary data obtained from other parties indirectly from the subject of information sources namely teacher grade 5. Data collection was obtained using studying 5th grade students while at home, besides using study studios that are used to obtain data consisting of instruments that relate to students who are learning and learning mathematics in class 5. The population in this study offers 13 students divided into 8 women and 5 men male class 5 at SD Negeri Ledok 06. The results of the study show: 1. There is a positive influence between improving learning and mathematics learning outcomes, 2. Students who rank 1-5 have a higher learning duration compared to students who have short learning advantages.